Obtaining the electrical impedance phase using Wavelet transform and Fourier transform from transient signals. Part 2: practical assessment and validation (2018)
This article presents a practical assessment and validation of the new proposed approach based on the continuous wavelet transform (CWT) to obtain the electrical impedance phase from online transient signals for a real transformer. Besides the mathematical procedure presented in a previous paper, an electronic system was also designed and implemented, in order to inject superimposed controlled pulses to the power system (50/60 Hz) wave. The results show improved performance of the wavelet transform compared to that of the Fourier Transform, for transient signal analysis to be applied on a nonintrusive transformer monitoring approach. Particularly, this new approach proves useful in overcoming problems related to signal filtering and signal processing in an online frequency-response analysis of a transformer diagnosis.